Highlighting the trajectory from intrauterine growth restriction to future obesity - Gantenbein, Katherina Vicky; Kanaka-Gantenbein, Christina (Frontiers in Endocrinology, 2022)
During the last decades several lines of evidence reported the association of an adverse intrauterine environment, leading to intrauterine restriction, with future disease, such as obesity and metabolic syndrome, both leading to increased cardiovascular and cancer risk. The underlying explanation for this association has firstly been expressed by the Barker’s hypothesis, the “thrifty phenotype hypothesis”. According to this hypothesis, a fetus facing an adverse intrauterine environment adapts to this environment through a reprogramming of its endocrine-metabolic status, during the crucial window of developmental plasticity to save energy for survival, providing less energy and nutrients to the organs that are not essential for survival. This theory evolved to the concept of the developmental origin of health and disease (DOHaD). Thus, in the setting of an adverse, f. ex. protein restricted intrauterine environment, while the energy is mainly directed to the brain, the peripheral organs, f.ex. the muscles and the liver undergo an adaptation that is expressed through insulin resistance. The adaptation at the hepatic level predisposes to future dyslipidemia, the modifications at the vascular level to endothelial damage and future hypertension and, overall, through the insulin resistance to the development of metabolic syndrome. All these adaptations are suggested to take place through epigenetic modifications of the expression of genes without change of their amino-acid sequence. The epigenetic modifications leading to future obesity and cardiovascular risk are thought to induce appetite dysregulation, promoting food intake and adipogenesis, facilitating obesity development. The epigenetic modifications may even persist into the next generation even though the subsequent generation has not been exposed to an adverse intrauterine environment, a notion defined as the “intergenerational transfer of environmental information”. As a consequence, if the increased public health burden and costs of non-communicable chronic diseases such as obesity, hypertension, metabolic syndrome and type 2 diabetes have to be minimized, special attention should be laid to the healthy lifestyle habits of women of reproductive age, including healthy diet and physical activity to be established long before any pregnancy takes place in order to provide the best conditions for both somatic and mental health of future generations